Clogging process by suspended solids during groundwater artificial recharge: Evidence from lab simulations and numerical modelling. Issue 25 (22nd August 2019) - Chu, Tong; Yang, Yuesuo; Lu, Ying; Du, Xinqiang; Ye, Xueyan
Abstract: Permeability reduction of infiltration media due to suspended solid (SS) clogging is the bane of groundwater artificial recharge. To overcome the clogging problem and advance the understanding of the process‐based spatial‐temporal evolution of SS clogging, a 1D laboratory column simulation was carried out, followed by numerical modelling of the experimental data in this study. It was found that clogging caused a reduction in the hydraulic conductivity ( K ) in the upper layer at the beginning and extended deeper to approximately 50 cm, and no reduction in K was detected below 52 cm throughout the experimental period of 129 hr. The most clogged layer spanned from the surface to a depth of 11 cm, and the middle 11–52 cm was characterized by a slight decrease in K. The clogging rates of the different layers decreased with the depth, which was based on data analysis, with the largest value of 0.038 hr −1 in the upper 1 cm. The overall K began to decrease from the surface layer and was increasingly affected by clogging with time. A mathematical model was established to simulate the SS clogging process evolution based on considerations of the attachments and detachments of particles. Then the model was applied to perform several scenario analyses after calibration and validation using the data obtained in the experiment. The simulation results indicated that the SS concentration was much more sensitive than the groundwater depth below the land surface, and 10 days of constant recharge is recommended as the disposal cycle of the clogged layer under the given conditions. Abstract : Based on conceptual model of groundwater artificial recharge by surface infiltration, 1D sand column experiment was conducted with constant head at both ends. Spatial‐temporal changes of hydraulic conductivity presented decrease of clogging rate with depth, which governed by suspended solid (SS) deposition and transport in porous media. Such evolution was numerically simulated by a new coupling mathematical model involved Darcy's flow equation, transport and kinetic attachment–detachment equation of SSs, and porosity‐dependent equation of hydraulic conductivity with particle deposition.